Perfil epidemiológico de parturientes submetidas à cesariana na maternidade de um hospital escola de Botucatu-SP - Neves, Ana Paula Amâncio [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
During the pregnancy process, the maternal organism commonly undergoes changes. Such changes follow the normal course of pregnancy; however, some maternal or fetal factors can interfere with pregnancy and adversely affect its outcomes, thus triggering what is referred to as high-risk pregnancy, which is responsible for increasing maternal, fetal or newborns’ morbimortality rates1,2. One of the obstetric alternatives for a safe resolution of this pregnancy type is the caesarean section. Nevertheless, an expressive increase in the number of caesarean sections has been observed worldwide, and they are, many times, unnecessarily indicated8. The world Health Organization (WHO) recommends that the total number of caesarean sections in relation to the total number of deliveries performed at health service should be a maximum of 15% 11, a limit that is easily surpassed in various services. To outline the epidemiological profile of pregnant women submitted to caesarean sections at a reference health care service in the city of Botucatu-SP. This is a cross-sectional, retrospective, exploratory, descriptive, quantitative study. The target population consisted of one hundred pregnant women assisted in this institution, who had been submitted to caesarean sections in 2010 and were randomly selected to compose the sample. In the analyzed period, there were 1,189 deliveries, of which 601 (50.5%) were natural deliveries, 588 (49.4%) were caesarean sections. As regards maternal age, 76% were in the age range of 19 to 36 years. A high percentage of patients (27%) had not completed elementary education and did not have a paid job; 67% were homemakers. Most of the participants were married (56%); 34% of the women were primiparas, but 19% were in their fourth or more pregnancies. Concerning prenatal care, little was found, since many of them had consultations out of the institution which were not recorded... (Complete abstract click electronic access below)

Durante o processo gestacional é comum ocorrerem mudanças no organismo materno, essas mudanças acompanham o curso normal da gravidez, porém alguns fatores maternos ou fetais podem interferir na gestação e afetar adversamente o resultado da mesma, desencadeando o que chamamos de gestação de alto risco, responsável por aumentar os índices de morbimortalidade materna, fetal ou do lactente1,2. Uma das alternativas obstétricas para resolução segura desse tipo de gestação é o parto cesárea, contudo nota-se um aumento expressivo no seu número no mundo todo, sendo muitas vezes desnecessariamente indicada8. A Organização Mundial da Saúde (OMS) preconiza que o total de partos cesáreos em relação ao número total de partos realizados em um serviço de saúde seja no máximo de 15% 11, limite facilmente ultrapassado em vários serviços. Traçar o perfil epidemiológico de gestantes submetidas à cesariana num Serviço de Saúde de referência, da cidade de Botucatu-SP. Estudo transversal, retrospectivo, exploratório, descritivo e de abordagem quantitativa. A população alvo constituiu-se de cem gestantes atendidas nessa instituição, sorteadas aleatoriamente, e que foram submetidas à cesariana no ano de 2010. No período analisado ocorreram 1189 partos, destes 601 (50,5%) foram partos normais e 588 (49,4%) partos cesáreas. Quanto à idade materna, 76% encontravam-se na faixa etária de 19 a 36 anos. Percentual elevado (27%) dos pacientes não tinha nem o primeiro grau completo e não exerciam trabalho remunerado, sendo que 67% delas são responsáveis por atividades do lar. A maioria era casada (56%), 34% das mulheres eram primíparas, porém 19% estavam na quarta ou mais gestações. Quanto ao pré-natal pouco foi encontrado, pois muitas realizaram as consultas fora da instituição e não foram registradas no prontuário do HC. Quanto à idade gestacional e realização... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cesariana; Epidemiologia; Hospitais Serviços de maternidade